Improvement Desain pada Sistem Pedal Mesin Press Hidrolik untuk Meningkatkan Keamanan dalam Operasional - Ananda Raka Surya M; Jonatan Antonio M; Setia Rini G; Handi Wilujeng Nugroho; Kurniawan Hamidi; Rama Dani Eka Putra; Tessa Zulenia Fitri (UNIB Press, 2025)
The hydraulic press machine is one of the essential tools in the manufacturing industry, particularly in the automotive sector, to accelerate and simplify the process of forming and assembling metal components with high precision. However, operating the machine using buttons presents several challenges, such as unresponsiveness, operator fatigue, and the risk of workplace accidents. This study aims to improve the efficiency and safety of hydraulic press machine operations by replacing the button system with a pedal system. This research uses a quantitative descriptive approach with literature review and experimental methods in the design process. The research stages include data collection through literature review, component Benchmarking to compile the Bill of Material (BOM), and machine design development using Assembly chart and Operation Process Chart (OPC). The results show that replacing buttons with pedals improves the machine's responsiveness and operator comfort. The ergonomic pedal design allows operators to control the machine more accurately and steadily, making the production process more efficient and consistent. Furthermore, the updated machine design with an enclosed structure enhances protection for internal components and extends the machine’s lifespan. In conclusion, the innovation of replacing the button system with a pedal system in hydraulic press machines successfully improves operator safety.